A new species of Setostylus Matile and new records of Setostylus bellulus (Williston) (Diptera: Keroplatidae) - Huerta, Heron; Fitzgerald, Scott J. (Zootaxa, 2020)
Setostylus xoxo spec. nov., is described and illustrated from Morelos, Mexico and southern Arizona, USA and is compared with similar Neotropical congeners. Additionally, the first records of Setostylus bellulus (Williston) are provided from Guatemala and Costa Rica and an updated key to the New World species of Setostylus is presented.